Impact of different types of resuscitation fluids on coagulation and continuous venovenous hemofiltration hemocompatibility in a porcine model - Bedarf, Janis Rebecca; Grosch-Ott, Sascha; Russ, Martin; Wagner, Johanna-Josophina; Hiebl, Bernhard; Kirschfink, Michael; Unger, Juliane Katharina (Therapeutic apheresis and dialysis, 2013)
Anticoagulation;Coagulation;Colloids;Continuous venovenous hemofiltration;Hemofiltration;Renal replacement